Women's Rights program outline (1968)
This document outlines a Women's Rights program adopted by the California Democratic Council Convention on March 17, 1968, and incorporated into its platform. It calls for a constitutional amendment guaranteeing equal rights for women and advocates comprehensive reforms in employment, including equal pay, anti-discrimination protections, maternity leave, and fair labor standards. The program also supports women's reproductive rights, including access to birth control information, removal of abortion prohibitions, and modernization of prostitution laws with an emphasis on rehabilitation. It urges expanded educational and job opportunities, publicly funded child-care centers, tax deductions for child-care expenses, and reforms to marriage, divorce, and property laws. Finally, it promotes integrating women fully into political party structures, increasing their representation in decision-making roles, encouraging women to seek public office, and combating media portrayals that undermine women's dignity.